Influence of pH and Fluoride Species on the Corrosion Behavior of Ti-xNb-13Zr Alloys in Ringer's Solution. (28th December 2013) - Robin, A.; Carvalho, O. A. S.
Abstract : Ti-Nb-Zr alloys are interesting materials for implant applications due to the atoxic character of the Nb and Zr alloying elements and to their low elastic modulus when compared to CP-Ti. In this work, the corrosion behaviour of CP-Ti, Ti-5Nb-13Zr, Ti-13Nb-13Zr, and Ti-20Nb-13Zr alloys was investigated in Ringer's solution of pH 2, 5, and 7.5 without fluorides and containing 1000 ppm F at 37°C, through open-circuit potential measurements, potentiodynamic polarization, and electrochemical impedance spectroscopy. The four materials showed a passive behavior in Ringer's solution without fluorides for pH ranging from 2 to 7.5 and in Ringer's solution of pH 5 and 7.5 containing 1000 ppm F but presented an active behavior in Ringer's solution of pH 2 containing fluorides. The corrosion resistance of all materials in Ringer's solution decreases with both decrease of pH and addition of fluorides. Ti-13Nb-13Zr alloy is a little more corrosion resistant than the Ti-5Nb-13Zr and Ti-20Nb-13Zr alloys and, in most conditions, the Ti-Nb-Zr alloys present higher corrosion resistance than CP-Ti.